The Cylon (Kylon) Coup in the City-State of Athens (632 B.C.) - Swadi, Khaled Naji (Thi Qar Arts Journal, 2025)
The study of the political history of Greece in general and the city-state of Athens in particular provides us with an image of both social and political conditions, as they are intertwined in the life of the individual. The city-state of Athens (Polis) witnessed pivotal changes in the fundamental aspects of Greek citizens’ lives, which had a direct impact on the emergence of political conflicts. One such conflict was the Cylonian conspiracy, which occurred after all the elements necessary for a political coup were in place. However, it failed shortly after it began due to a lack of support and backing. This abandonment came not only from the nobles and those with wealth and power but also from the general populace, including farmers. The latter had a subtle influence on the course of events at that time, as they formed the popular base upon which both old and new political systems were built.